SOLVING OF A NEUMANN BOUNDARY VALUE PROBLEM THROUGH VARIATIONAL METHODS - Haghshenas, Hadi; Afrouzi, Ghasem A (TWMS journal of applied and engineering mathematics, 2020)
In this work, applying the multiple critical points theorems, we obtain the existence results of two and three classical solutions for a Neumann boundary value problem with the Sturm-Liouville equation.